Modelo social cognitivo de satisfação no trabalho e eficácia coletiva: percepções sobre a docência - RAMOS, Maély Ferreira Holanda (Universidade Federal do Pará, 2020)
This research aims to study job satisfaction from the Social Cognitive Model of Job Satisfaction (MSCST) and its relations with the collective efficacy. The satisfaction and their main elements which influence have obvious importance in the school context because it may affect the motivational states and the level of the teacher’s performance. Job satisfaction refers to the degree of emotional relations that an employee has, associated to function that performs, showing a pleasant or positive emotional state, resulting from an assessment of their experiences. The Social Cognitive Model of Job Satisfaction is a recent proposal, which is based on Social Cognitive Theory that proposes an integrative approach to investigate the satisfaction in teaching. This theory reveals that satisfaction can be predicted and explained by five variables classes, namely: (a) support targets; (B) working conditions; (C) Progress goals; (D) positive affect; (E) teaching self-efficacy. The teacher collective efficacy, although not belonging to the model, also has recognized influence on levels of satisfaction. So it has the general objective of testing the Social Cognitive Model of Teacher Job Satisfaction (MSCST) in sample of teachers of basic education, investigating its relations with the collective efficacy and analyzing their implications in the school environment. For that, we developed six articles arranged in two subdivisions, which are: (a) Systematic Reviews; (b) Empirical Studies. The first section consists of four articles, which include a methodological study on the use of technical analysis and visualization of data with graphs and three systematic reviews on: MSCST, job satisfaction and collective efficacy (respectively). All the revisions used graphs and their geometric representations. The second subdivision, consisting of two articles, referring to empirical studies, applied to a sample of 495 teachers of basic education from a private school network. The first study of this section was quantitative and the second used mixed techniques (quantitative and qualitative). The results indicated that MSCST did not explain sufficiently the satisfaction in teaching, contradicting the findings found from the systematic review of the Model. It was also found that there was no relations between efficacy beliefs (self-efficacy and collective efficacy) with the levels of satisfaction, although research identified in systematic reviews, which have not implemented the model, pointed out these two variables as more often associated with satisfaction teaching.